Energy transition under twin shocks: Geopolitical and macrofinancial risks - Ulug, M.; Andrei, R. (Energy Economics, 2025)
The Greater North European Energy Corridor (GNEEC) – comprising Belgium, Denmark, Finland, Germany, the Netherlands, Norway, Sweden, and the United Kingdom - stands as a vital core for Europe’s renewable energy ambitions, while facing rising geopolitical and macro-financial pressures. This study explores how Composite Geopolitical Risk (CGR) and macro-financial pressure have driven the energy transition within the GNEEC from 1990 to 2023, alongside the roles of economic growth and environmental innovation. Using the Method of Moments Quantile Regression (MMQR) approach, the results reveal strong heterogeneity along the green transition pathway. CGR has a consistently positive and rising effect on renewable deployment ( ≈ 1.05 at ? = 0.1 to ≈ 1.81 at ? = 0.9), showing that geopolitical tensions accelerate diversification, especially among transition leaders. In contrast, macro-financial pressures driven by monetary tightening hinder renewables ( ≈ 0.44 at ? = 0.1 to ≈ 0.27 at ? = 0.9), with financing costs constraining early-stage adopters more severely. Similarly, economic growth slows the clean share ( ≈ 77 at ? = 0.1 to ≈ 1.25 at ? = 0.9), as rebound and scale effects outweigh short-term efficiency gains. Environmental innovation fosters renewables at lower quantiles ( ≈ 1.50 at ? = 0.1 to ≈ 0.73 at ? = 0.9) but becomes insignificant at advanced stages, reflecting diminishing marginal returns. These findings highlight structural asymmetries: leaders convert geopolitical risk into faster deployment, while laggards remain more vulnerable to financial constraints. The study offers clear policy implications, including strengthening de-risking mechanisms, aligning growth with low-carbon strategies, and fostering innovation diffusion, in order to balance energy resilience, security, and financial sustainability across varying stages of the transition.